(untitled) (Acta Scientiarum. Animal Sciences, 2020)
The objective of this study was to evaluate productive performance and egg quality of Japanese quails (Cortunix japonica) fed with synthetic and natural pigments. The treatments used were: 0.8% paprika extract (Capsicum annuum), 0.8% marigold flower extract, 4% paprika extract and 4% marigold flower extract and 0.045% synthetic pigment (Canthaxanthin) in feed. A total of 240 Japanese quails at 20 weeks of age were distributed in a completely randomized experimental design with five treatments and six replicates, with eight quails per experimental unit (30 experimental units). There was no difference (p > 0.05) for the evaluated parameters, except for yolk color which showed significant difference (p < 0.05) between the treatments used. The inclusion of 0.8% natural pigments in diet of Japanese quails can be used to substitute canthaxathin because it is effective on improving yolk color without affect performance and the quails egg quality.